2018
DOI: 10.1111/jmft.12370
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Similarity and Stability of Differentiation in Relationships: A Dyadic Study of Bowen's Theory

Abstract: Bowen family systems theory (BFST) identifies differentiation of self as a crucial characteristic that relates to one's individual and relational maturity. Bowen theorizes that an individual's level of differentiation typically remains static over time and that individuals select and pair in relationships with others who have similar levels of differentiation. This study aimed to test the hypotheses of BFST by using components of differentiation of self, emotional reactivity, and emotional cutoff, in dyadic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(23 reference statements)
0
5
2
Order By: Relevance
“…Conversely, the solid self is characterized by more consistent conviction and more stability over time, and individuals with higher levels of DoS are postulated to operate from a place of the solid self [ 14 , 29 ]. Handley and colleagues found more stability (less change) in DoS over time with their sample [ 26 ], while the current study found a significant increase in DoS over time in both men and women and in both cultures. Notably, Handley and colleagues used yearly intervals in their assessment of changes in DoS [ 26 ], while the current study had a much longer interval between the two time points assessed (four years in the U.S. sample, seven years in the Spanish sample).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Conversely, the solid self is characterized by more consistent conviction and more stability over time, and individuals with higher levels of DoS are postulated to operate from a place of the solid self [ 14 , 29 ]. Handley and colleagues found more stability (less change) in DoS over time with their sample [ 26 ], while the current study found a significant increase in DoS over time in both men and women and in both cultures. Notably, Handley and colleagues used yearly intervals in their assessment of changes in DoS [ 26 ], while the current study had a much longer interval between the two time points assessed (four years in the U.S. sample, seven years in the Spanish sample).…”
Section: Discussioncontrasting
confidence: 54%
“…Handley and colleagues found more stability (less change) in DoS over time with their sample [ 26 ], while the current study found a significant increase in DoS over time in both men and women and in both cultures. Notably, Handley and colleagues used yearly intervals in their assessment of changes in DoS [ 26 ], while the current study had a much longer interval between the two time points assessed (four years in the U.S. sample, seven years in the Spanish sample). It is possible that in the current sample, the greater amount of time between assessments of DoS was an important factor in forming a more solid self, particularly during a time of stressful events.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…There is thus a potential risk that members of dyads have influenced each other's answers without the research team knowing about it. Secondly, even if the participants answered the questionnaires completely independently, there is a risk that the partner's scores are related because individuals select and pair with others who are similar to themselves in how to form relations (35). However, this was accounted for in the mixed-effects logistic regression analyses.…”
Section: Methodological Limitationsmentioning
confidence: 99%